Compression garment promotes muscular strength recovery after resistance exercise - Goto, K.; Morishima, T. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to investigate the effects of wearing a compression garment (CG) for 24 h on changes in muscular strength and blood parameters over time after resistance exercise.